Impacts of the mathematical clinic in the academic performance of the students (2019)
The article present the scopes of the pedagogic model called "mathematical clinic" evaluated in students of fourth and fifth grade of the "Escuela Sagrado Corazón de Jesús, San José de Cúcuta, Colombia", which has as principal aim analyse the impacts that the initiative had in the rate of academic mortality, those who on not having graduated of primary with an appropriation consolidated of the mathematics have difficulties in their performance during the following years. The methodology of the study is quantitative, correlational, since from the assistance, approval and disapproval his incident is calculated in the performance of the pupils. The results reflect high correlation, where the clinic has turned into a space effective learning in the institution into that students strengthened their interest for the different areas of knowledge.